2011
DOI: 10.22358/jafs/66172/2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish oil on NF<sub>κ</sub>B gene expression and related signaling in spleen of chickens stimulated with lipopolysaccharide

et al.

Abstract: The study was conducted to investigate the effects of fish oil and maize oil on nuclear factor kappa B (NFκB) gene expression and the downstream pathways of intracellular signaling in spleen of chickens after lipopolysaccharide (LPS) stimulation. Two hundred eighty eight chickens were assigned in a 2×2 factorial design. Factors were dietary fat type (4.5% maize oil or 4.5% fish oil) and immunological stimulation (LPS or saline). LPS increased levels of eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Nuclear factor kappa B (NFκB) gene expression and the downstream pathways of intracellular signalling in spleen following LPS challenge Alleviated immune stress, i.e., reduced PGE 2 production, activity of cyclooxygenase 2, and activity of phospholipase C in the spleen; alleviated mRNA abundance elevation of NFκB following LPS stimulation in birds fed diets with fish oil Yang et al (2011) Fish oil (0%, 1.5%, 3%, or 6% in the diet) Broiler chickens…”
Section: Antibody Titres Against Sheep Red Blood Cells (Srbc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor kappa B (NFκB) gene expression and the downstream pathways of intracellular signalling in spleen following LPS challenge Alleviated immune stress, i.e., reduced PGE 2 production, activity of cyclooxygenase 2, and activity of phospholipase C in the spleen; alleviated mRNA abundance elevation of NFκB following LPS stimulation in birds fed diets with fish oil Yang et al (2011) Fish oil (0%, 1.5%, 3%, or 6% in the diet) Broiler chickens…”
Section: Antibody Titres Against Sheep Red Blood Cells (Srbc)mentioning
confidence: 99%
“…To compare the effect of dietary sources of n-6 and n-3 PUFAs on nuclear factor kappa B (NFκB) gene expression and downstream pathways of intracellular signalling in spleens of chickens following LPS stimulation, Yang et al (2011) supplemented the diet with maize or fish oil. They found that dietary fish oil reduced PGE2 production, cyclooxygenase 2 activity, and phospholipase C activity in spleens, as well as alleviated the mRNA abundance elevation of NFκB following LPS stimulation.…”
Section: Broiler Chickensmentioning
confidence: 99%
“…The B-lymphocytes were collected after a 72-h culture period. The IP 3 content of the cell culture medium was detected using an ELISA kit according to manufacturer's instructions (Yang et al, 2011).…”
Section: Elisamentioning
confidence: 99%
“…Docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are the principal n-3 polyunsaturated fatty acids (PUFAs) in fish oil. These eicosanoids have a wide range of biological activities, including effects on cell proliferation and differentiation, as well as the immune system (Calder, 2008;Wang et al, 2011;Yaqoob, 2003;Yang et al, 2011). Hwang (2000) suggested that n-3 PUFA altered eicosanoid metabolism, phosphatidylinositol signalling pathway of lymphocytes, or both.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation